RF and microwave photonic temporal signal processing with Kerr micro-combs - Tan, Mengxi; Xu, Xingyuan; Wu, Jiayang; Morandotti, Roberto; Mitchell, Arnan; Moss, David J. (Advances in physics: X, 2021)
Integrated Kerr micro-combs are a powerful source of multiple wavelength channels for photonic radio frequency (RF) and microwave signal processing, particularly for transversal filter systems. They offer significant advantages featuring a compact device footprint, high versatility, large numbers of wavelengths, and wide Nyquist bands. We review progress on photonic RF and microwave high bandwidth temporal signal processing based on Kerr micro-combs with comb spacings from 49 GHz to 200 GHz. We focus on integral and fractional Hilbert transforms, differentiators as well as integrators. The future potential of optical micro-combs for RF photonic applications in terms of functionality and ability to realize integrated solutions is also discussed.